PENGARUH PENAMBAHAN UREA DAN AMONIUM KARBONAT PADA PEREKAT UREA FORMAIDEHIDA TERHADAP EMISI FORMALDEHIDA DAN SIFAT FISIS-MEKANIS PAPAN PARTIKEL - Paribotro Sutigno; Adl Santoso (Jurnal Penelitian Hasil Hutan, 1991)
The  formaldehye  emission  of  particleboard  bonded   with  urea  formaldehyde  (UFJ  cain  affect  human  hseith. sepecially if It  used  in a room with limited ventilation. To reduce formaldehyde emission,  the glue can be  mixed with catching agent.  In  this paper, the effect  of  using  urea and  ammonium carbonate as catching agents  on   fermaldehyde emission,and on the physical and mechanical properties of UF bonded particleboard  is described.the effect of catching agent type on formaldehyde emission is not signifivant while effect of percentage,of catching agent is highly significant on formaldehyde emission. The higher  the percentage  of catching agent, the lower  formaldehye emission of particleboard. The formaldehyde emission reaches  the requirement (max. 1  ug/ml) at the leve of  18% of amntonium carbonate or 14%  of the mixture of ammonium carbonate and urea. Type  and percentage of catching agent aflect   water absoprtion, thickness  swelling, internal bond strength,shear  strength and modulus of rupture,but not the modulus of elasticity.